"PMA Sounds Fun": Negotiating Drug Discourses Online. (3rd July 2014) - Barratt, Monica J.; Allen, Matthew; Lenton, Simon
Abstract : In 2007, a young woman, Annabel Catt, died after consuming a capsule sold as "ecstasy" that contained para-methoxyamphetamine. In this paper, we describe how this death was depicted in online drug-user communities and illustrate how the meanings of drug use are negotiated in online settings. News articles, public online discussions, and online fieldwork formed the data. This paper demonstrates how dominant drug discourses may be resisted by drug users, drawing on theories of health resistance and Kane Race's concept of counterpublic health. Online environments may offer ways of engaging people who use drugs that acknowledge both pleasure and safety. The study's limitations are noted.